Extrarenal Pyelocalyceal System or Extrarenal Calyces: A Case Series and Literature Review - Namasivayam Selvarajan; B.R. Nammalwar; Sairam V Kannan; S. Muralinath; Rochita Venkataramanan; Madhu Ramasundaram; Senthil Ganesh Kamaraj; Jai Durai Raj; G. Nandhini; Vidhya Tamizhvanan (Journal of Indian Association of Pediatric Surgeons)
Extrarenal pyelocalyceal system or extrarenal calyces, a congenital anomaly, is identified when it presents with pelviureteric junction obstruction. It is elusive to preoperative diagnosis and was identified only intraoperatively in all published pediatric cases. Experience gained by managing a series of cases and a literature search has guided us to evolve a preoperative diagnostic approach, a pyelotomy technique, and a practical classification of the EPS. During the period from 2003 to 2023, four cases with six kidneys of the EPS including three kidneys of the polar extrarenal infundibulum and calyces, a variant of EPS involving only upper or lower pole of the kidney, were seen. Successful pyeloplasty was performed in five of the six kidneys for PUJO using a careful pyelotomy technique. Characteristic “garden rake” X-ray sign was seen in intravenous urogram or retrograde pyelogram, contrast-enhanced computerized tomogram, or magnetic resonance imaging (MRI) of the abdomen in three kidneys. Retrograde pyelogram, CECT, or MRI of the abdomen identified the polar variant in three kidneys. Late-onset PUJO was seen in one case. Four cases with PUJO presented with significantly reduced renal function. One showed postoperative deterioration to nonfunction despite good drainage. A preoperative diagnostic approach, a pyelotomy technique for pyeloplasty, and a classification of the EPS are evolved by the authors. Progressive loss of function and late-onset obstruction mandate a renal-sparing pyeloplasty approach and follow-up.